Study Dan Kompilasi Data Tentang Desalinasi Air Industri - Karsini Karsini (Balai Besar Kimia dan Kemasan, 1977)
Study and data compilation about industrial water desalination will be described in this paper. The experiments have been made on brakish waters, carried out by Industrial Research Institute in Jakarta. Prototype of electrodialysis appar atus has also been studied by Industrial Reserch Institute.